Polarization Label-Free Microscopy Imaging of Biological Samples by Exploiting the Zeeman Laser Emission - Callegari, Fabio; Le Gratiet, Aymeric; Zunino, Alessandro; Mohebi, Ali; Bianchini, Paolo; Diaspro, Alberto (Frontiers in Physics, 2021)
Mueller Matrix Microscopy exploits the generation and the analysis of polarized light to create label-free contrast in biological images. However, when dealing with Optical Scanning Microscopy, it is required a fast generation of the polarization states in order to obtain a good Signal-to-Noise Ratio at the pixel-dwell time rate. In this work, we propose a microscopy system based on a scanning beam architecture that is exploiting the simultaneous emission of orthogonal polarization states from a Zeeman laser to provide Mueller Matrix images. This approach is based on the detection of an interference signal that allows to time-encode polarization states directly from the laser source, without the need for further active components for the management of the polarization states. We provide the theoretical model behind this approach and we apply our new method to the imaging of biological samples. Our Mueller Matrix imaging setup enables high-speed scanning microscopy, while preserving compactness and simplicity of construction. Our findings may lead to more effective dissemination of label-free techniques and their use by biological researchers.